(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
The Ayurvedic formulary has a long history of endogenous innovation. Its epistemic logic is best understood through the language of Oushadhayogam (polyherbal combination/ dosage forms). Punarnavadi kwatha (PUK) is an Ayurvedic polyherbal formulation, which is also known as Punarnavashtaka kwatha. It is generally used to treat diseases of respiratory system, bronchitis, liver diseases, hepatitis, joint inflammation, kidney stones, wounds, skin diseases, and gout. The present study intended to explore the Ethanobotanical diversity of Punarnavashtaka kwatha in Kerala Ayurveda market. Materials and Methods: Thorough search in classical Ayurvedic literature to collect data in PUK and cross-sectional survey to collect data of ingredients PUK used in Ayurveda industry. Results and Discussions: The ingredients of PUK along with botanical source of 5 Kerala Ayurveda manufactures were analysed and compared with AFI. The ingredients Punarnava, Nimba, Patola, Sunthi, Abhaya was common in all the manufactures. But marked variation in other ingredients were found in market samples of PUK when compared to AFI, except first sample. Conclusions: There are some ethanobotanical diversity in ingredient list of Punarnavadi kwatha (PUK) in Kerala Ayurveda market.